Operations management processes and supply chains - Krajewski, Lee J.; Ritzman, Larry P.; Malhotra, Manoj K. (Pearson Education, 2013)
This book balances presentation of corporate strategy and analytical tools by presenting decision-making within the context of a firm's competitive priorities. Two new chapters address supply-chain management and the management of technology, both very timely topics in production and operations management today.